Using zero watermarks for image authorship and multi-factor authentication - Poddubnyi, V.O.; Gvozdov, R.Y.; Sievierinov, O.V. (Radiotekhnika, 2024)
The relevance of this work lies in the revealed possibilities of using zero watermarks to confirm the authorship of digital images and the use of zero watermarks for images as a method of multifactor authentication. The paper proposes a modernized zero watermark algorithm for testing the capabilities of zero watermarks. The proposed multifactor authentication algorithm using zero watermarks. Tests have shown that null watermarks are not suitable for confirming authorship, as they cannot guarantee the distinction between similar images or between images of the same author. However, there is a prospect of using this technology in multi-factor authentication schemes, in combination with other authentication methods (such as password, biometrics, tokens).